Decreased blood glucose and lactate: Is a useful indicator of recovery ability in athletes? - Yang, W.-H.; Park, H.; Grau, M.; Heine, O. (International Journal of Environmental Research and Public Health, 2020)
During low-intensity exercise stages of the lactate threshold test, blood lactate concentrations gradually diminish due to the predominant utilization of total fat oxidation. However, it is unclear why blood glucose is also reduced in well-trained athletes who also exhibit decreased lactate concentrations. This review focuses on decreased glucose and lactate concentrations at low-exercise intensity performed in well-trained athletes. During low-intensity exercise, the accrued resting lactate may predominantly be transported via blood from the muscle cell to the liver/kidney. Accordingly, there is increased hepatic blood flow with relatively more hepatic glucose output than skeletal muscle glucose output. Hepatic lactate uptake and lactate output of skeletal muscle during recovery time remained similar which may support a predominant Cori cycle (re-synthesis). However, this pathway may be insufficient to produce the necessary glucose level because of the low concentration of lactate and the large energy source from fat. Furthermore, fatty acid oxidation activates key enzymes and hormonal responses of gluconeogenesis while glycolysis-related enzymes such as pyruvate dehydrogenase are allosterically inhibited. Decreased blood lactate and glucose in low-intensity exercise stages may be an indicator of recovery ability in well-trained athletes. Athletes of intermittent sports may need this recovery ability to successfully perform during competition.